2019
DOI: 10.1090/proc/14628
|View full text |Cite
|
Sign up to set email alerts
|

No topological condition implies equality of polynomial and rational hulls

Abstract: It is shown that no purely topological condition implies the equality of the polynomial and rational hulls of a set: For any uncountable, compact subset K of a Euclidean space, there exists a set X, in some C N , that is homeomorphic to K and is rationally convex but not polynomially convex. In addition, it is shown that for the surfaces in C 3 constructed by Izzo and Stout, whose polynomial hulls are nontrivial but contain no analytic discs, the polynomial and rational hulls coincide, thereby answering a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To show that b † D h r . †/, we use an argument due to Izzo, who showed in [22,Section 3] that E satisfies the generalized argument principle, i.e., if p is a polynomial that has a continuous logarithm on E, then 0 … p.E/. We now apply the following result due to Stolzenberg ([29]) to X D E and Y D B 0 .…”
Section: Proofs Of the Main Resultsmentioning
confidence: 99%
“…To show that b † D h r . †/, we use an argument due to Izzo, who showed in [22,Section 3] that E satisfies the generalized argument principle, i.e., if p is a polynomial that has a continuous logarithm on E, then 0 … p.E/. We now apply the following result due to Stolzenberg ([29]) to X D E and Y D B 0 .…”
Section: Proofs Of the Main Resultsmentioning
confidence: 99%
“…In [2], it is shown that if the embedding is also required to be totally real, then the optimal value of n is ⌊3m/2⌋, for any m ≥ 2. In [17], it is shown that the constructions in [18] and [2] can be done so that the rational and polynomial hulls of the embeddings coincide. In our next result, we show that the answer to the original question is strictly less than ⌊3m/2⌋ for even-dimensional manifolds.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…To show that Σ = h r (Σ), we use Izzo's argument from [17,Section 3]. He shows that the set E satisfies the generalized argument principle, i.e., if p is a polynomial that has a continuous logarithm on E, then 0 / ∈ p(E).…”
Section: Proof Of Proposition 13mentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the polynomial and rational hulls of X coincide. In contrast, the construction given here does not yield density of invertible elements, and as shown in the first author's paper [8], it can be used to obtain rationally convex examples.…”
Section: Introductionmentioning
confidence: 87%